Palanca awards - Carino, Ma. Luisa Aguilar (Animo Repository, 1997)
Four DLSU faculty won in the 1997 Palanca Awards. The awardees were Ma. Luisa Aguilar Carino in the English poetry category, Aurora Yumul, John Iremil Teodoro and Sid Gomez Hildawa in the full-length plays in Filipino.